1994
DOI: 10.1161/01.cir.89.3.1469
|View full text |Cite
|
Sign up to set email alerts
|

Guide to anticoagulant therapy. Part 2: Oral anticoagulants. American Heart Association.

Abstract: Drugs that increase the anticoagulant effect of warfarin without affecting its plasma levels include the second-and third-generation cephalosporins, which augment the anticoagulant effect of warfarin by inhibiting the cyclic interconversion of vitamin K18; clofibrate, Requests for reprints should be sent to the Office of Scientific Affairs, American Heart Association, 7272 Greenville Avenue, Dallas, TX 75231-4596. at NORTH DAKOTA STATE UNIV on June 26, 2015 http://circ.ahajournals.org/ Downloaded from pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
0
7

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(95 citation statements)
references
References 91 publications
0
88
0
7
Order By: Relevance
“…Anticoagulant therapy is the treatment of choice for most patients with DVT. Acute DVT is usually treated with a five-to-seven day course of intravenous unfractionated heparin (UFH) or subcutaneous low molecular weight heparin (LMWH), followed by at least three months of oral anticoagulant therapy [1][2][3]. LMWH have the potential advantage of allowing patients with uncomplicated DVT to be treated at home rather than in the hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Anticoagulant therapy is the treatment of choice for most patients with DVT. Acute DVT is usually treated with a five-to-seven day course of intravenous unfractionated heparin (UFH) or subcutaneous low molecular weight heparin (LMWH), followed by at least three months of oral anticoagulant therapy [1][2][3]. LMWH have the potential advantage of allowing patients with uncomplicated DVT to be treated at home rather than in the hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Ademais, a administração de vitamina K, especialmente por via intravenosa, pode tornar esse paciente refratário à ação do AVK por períodos longos, até de semanas 4 .…”
Section: Discussionunclassified
“…A administração de vitamina K é inadequada na maioria dos casos, pois são necessárias algumas horas até que se elevem os níveis de fatores de coagulação e se restabeleça a hemostasia. Além disto, a administração de vitamina K torna o paciente de risco para tromboembolismo refratário ao tratamento anticoagulante, após a resolução do processo hemorrágico 4 . A administração de PFC reverte mais rapidamente a hipocoagulabilidade nos pacientes com hemorragia cerebral, e deve ser usado em situações de emergência.…”
Section: Discussionunclassified
“…Anticoagulation is measured by the international normalized ratio (INR) or prothrombin time ratio (PTR). The American Heart Association (AHA) [2] and the American College of Chest Physicians [3] recommend a therapeutic level of anticoagulation of no higher than INR 3.5 or about PTR 2.0 (although other centers [4] have declared no higher than INR 4.0 or about PTR 2.2). A survey in 1996 revealed that 73% of physicians recommended withdrawing warfarin before some or all dental surgeries.…”
Section: Patients On Anticoagulant Drugsmentioning
confidence: 99%